Caracterização química comparativa e atividades biológicas dos polissacarídeos obtidos das partes aéreas e de cultura de calos de Cereus peruvianus Mill (CACTACEAE) - Tanaka, Leonardo Yugo Abe (2010)
The cactus known as "Mandacaru", Cereus peruvianus Mill. (Cactaceae), has many applications for economic purposes. Besides the plant, callus culture may also be an alternative source of polysaccharides. However, there is a lack of information regarding the chemical and biological application of polysaccharides from C. peruvianus. After obtaining the polysaccharides with distilled water followed by precipitation with ethanol, we obtained the raw plant polysaccharide (PP) and the polysaccharide gross callus (PC). Then the polysaccharides were subjected to the purification and partial characterization, obtaining the polysaccharide purified plant (PP2) and the polysaccharide purified from callus (PC2). The total carbohydrate in PP2 and PC2 was determined as being 24.97% and 30.41%, respectively, and the protein content of PP2 was 0.10% and 0.12% in PC2. The polysaccharide from aerial parts is composed of arabinose, galactose, rhamnose and uronic acid in the proportion of the callus and 66:15:6:13 by arabinose, galactose and rhamnose at a ratio of 95:3:2. Some biological activity tests were carried out between them anti-inflammatory, antiulcer and antiviral. Analysis antiviral against HSV-1 by sulphorodamine B colorimetric method showed that both polysaccharides showed low cytotoxicity (CC50 above 500 mg / ml for samples PP and PC; of 440.00 ± 59.22 mg / ml for PC2 and 483.33 ± 56.25 g / ml for PP2) and exhibited antiviral activity EC 50 around 16 g / ml for both samples (PP and PC). However this activity was not found in purified samples (PP2 and PC2). In the trial of anti-inflammatory activity, performed by the method of inhibition of ear edema induced by 12-O-Tetradecanoylphorbol-13-acetate (TPA), a reduction in the edema of 29 ± 5.0% for PP (100 mg / kg) and 51 ± 8.0% for PC (100 mg / kg). In the test of paw edema induced by TPA only the polysaccharide obtained from the callus showed ability to inhibit the edema (37 ± 9%). In the activity test antiulcer only the polysaccharide obtained from aerial parts (PP) was tested and showed significant activity with an ED50 of 49.0 mg.kg-1. It was observed that the polysaccharides obtained from plants and callus culture vary in their structures related to the content and composition of monomer sugars which explains the differences in their chemical, physical and pharmacological. Inhibition of gastric lesions and anti-inflammatory activity of PP may suggest the use of this polysaccharide purified or crude hydro-alcoholic extract of the stems of C. peruvianus in the form of a food additive.